PRODUKSI DAN KARAKTERISASI NANOSERAT SELULOSA ASETAT DENGAN METODE ELEKTROSPINING - Harahap, Mahyuni; Zai, Liver Iman Putra (Program Studi Kimia - Universitas Sari Mutiara Indonesia, 2022)
In this research, cellulose acetate fiber was produced by electrospinning method. Cellulose acetate was dissolved with acetone solvent and then putin to a cooling system torestrain the rate of evaporation of cellulose acetate. The conductivity and evaporation rate of the cellulose acetate solution were tested, and the cellulose acetate fiber sproduced were tested using scanning electron microscopy (SEM). The conductivity of the cellulose acetate solutionwas 3.45 S/cm at 15oC and almost doubled at 22oC. The cooling system test was ableto maintain the temperature of the cellulose acetate solution at 15 oC for approximately 2 minutes. In addition, bead fibers are produced due to their low conductivity.